PENERAPAN E-COMMERCE PADA USAHA BATIK JAMBI PADA TOKO BATIK DUO SERANGKAI: Customers, Promotion, E-Commerce, Batik. - Sany, Ezrifal; Kurniawan, Yudiyanto (JURNAL AKADEMIKA, 2023)
With today’s technological development, human activities are becoming more and more easy to do, as sales and sales activities have been broken down with what is called "e-commerce. E-commerce is an attempt to conduct trade transactions between sellers and buyers using the Internet. The development of information technology, especially in the field of the Internet, is a driving factor in the development of e-commerce. Using information technology, e-commerce can be used as a solution to help manufacturers face competitors. The objective of this final task is to create an e-commerce information system on the product of Duo Serangkai, which is a means of marketing and sales to develop business in the sale and purchase of products online that contains information about the product as well as the product ordering process. When designing this system, the authors use the concepts of object-oriented programming (OOP) and the unified modeling language (UML). The E-Commerce Information System that was used in this study performed admirably. Thus, it can be implemented by the product in terms of promotion and online sales, as well as managing all product data, report data, and user data..